Real rail adventures : Swiss international hubs [videorecording (DVD)] (Small World Productions, 2020)
"Jeff's adventures continue in Real Rail Adventures: Swiss International Hubs as he explores five international rail hubs in centrally located Switzerland and hops connections to Germany, France and Italy. Swiss cities Basel, Bellinzona, Geneva, Interlaken and Zurich are highlighted, and Jeff sets out to discover seamless train connections to Paris, Milan, and Hamburg as well."--Smarttravels.tv